Perkembangan Penegakan Hukum terhadap Tindak Pidana Korupsi di Indonesia - Ni Putu Sri Widiasih (Jurnal Ilmu Sosial dan Humaniora, 2026)
The enforcement of laws against corruption in Indonesia has undergone significant development following regulatory and institutional reforms since the reform era. Various legal frameworks and anti-corruption institutions have been established to strengthen efforts in combating corruption. Nevertheless, in practice, the enforcement of corruption laws continues to face substantial challenges and obstacles. These include issues related to regulatory coherence, institutional effectiveness, political influence, and the prevailing legal culture, all of which affect the overall performance of anti-corruption law enforcement. This study employs a normative juridical method with statutory and conceptual approaches to examine the development of corruption law enforcement in Indonesia, identify the existing challenges and obstacles, and formulate relevant solutions for strengthening the enforcement of anti-corruption laws. The study finds that strengthening legal regulations, enhancing the independence and integrity of law enforcement agencies, optimizing asset confiscation, and reinforcing preventive measures constitute essential strategies for improving the effectiveness of anti-corruption law enforcement.